The Effect of Association between Fat Mass and Obesity-associated Gene Polymorphism (rs9939609) on the Body Composition of Older People: A Systematic Review - Trevisano, Rebeca Gonçalves; Gregnani, Marcos F.; de Azevedo, Bruna Cestari; de Almeida, Sandro Soares (Current Aging Science, 2022)
Background: The aging population is growing faster than any other age group worldwide. Associated with aging, the prevalence of overweight and obesity is a potential risk factor for the development and aggravation of numerous pathologies. A genetic factor often associated with obesity is the fat mass and obesity-associated (FTO) (rs9939609) gene polymorphism, which has been extensively investigated in children, young, and adults. However, few studies have been carried out on the older population. This review aimed to verify the influence of the FTO (rs9939609) gene polymorphism on the body composition of the older population. Methods: We conducted a systematic review and meta-analysis on PubMed, Scielo, and LILACS databases. Statistical analysis for meta-analysis was performed using mean values of Body Mass Index (BMI) and standard deviations. Results: The results did not show significant differences between FTO genotypes and BMI values (-0.32, 95% CI -0.45 to -0.19, I2 = 0%, p = 0.52). However, 59% of the studies identified some influence on body composition, obesity, or comorbidities. Conclusion: Few publications verify FTO polymorphism effects on specific groups of the older population, suggesting a reduction in the influence of this gene on the BMI with advancing age. However, we believe that more controlled studies in older populations should be performed.
Keywords: Aging